2020
DOI: 10.1101/2020.10.20.20216119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Impact of Mitigation Policies and Socioeconomic Status on COVID-19 Prevalence and Social Distancing in the United States

Abstract: Background The spread of COVID-19 has highlighted the long-standing health inequalities across the U.S. as neighborhoods with fewer resources were associated with higher rates of COVID-19 transmission. Although the stay-at-home order was one of the most effective methods to contain its spread, residents in lower-income neighborhoods faced barriers to practicing social distancing. We aimed to quantify the differential impact of stay-at-home policy on COVID-19 transmission and residents mobility across neighborh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, some previous studies have shown that social distancing is more difficult in socio-economically disadvantaged neighbourhoods where crowding results in individuals or communities to be more likely to be exposed to COVID-19. 38 , 39 , 40 , 41 With most participants living below the international poverty line of $1.90 per day, 42 the fight against the pandemic becomes more complex and problematic. The impact of the economy on the COVID-19 fight has been also reported elsewhere in the world.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some previous studies have shown that social distancing is more difficult in socio-economically disadvantaged neighbourhoods where crowding results in individuals or communities to be more likely to be exposed to COVID-19. 38 , 39 , 40 , 41 With most participants living below the international poverty line of $1.90 per day, 42 the fight against the pandemic becomes more complex and problematic. The impact of the economy on the COVID-19 fight has been also reported elsewhere in the world.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential reasons for the differences observed between younger and older children. Studies have shown age-related differences in transmission risk within households, 9 and an increased risk of COVID-19 transmission from secondary schools versus primary schools. 4 We speculate that younger children may be more likely than older children to contract COVID-19 at home than school.…”
Section: Discussionmentioning
confidence: 99%
“…These models were designed to address confounding by transmission to children from adults and the effects of SES (which is independently associated with COVID-19 rates) on transmission. 9 Models included: (1) an unadjusted model including only ESOS; (2) an adult-adjusted model including ESOS and the log 2 incidence of COVID-19 in adults aged 20-59 (to account for every doubling of local adult incidence); and (3) a full model adding SES to the adult-adjusted model. The adult-adjusted and full models did not include counties with no adult cases of COVID-19 as modeling the effect of adult COVID-19 transmission does not make sense when there is no transmission.…”
Section: Methodsmentioning
confidence: 99%